Treatment of Highland Frogs from the Two-Legged Stage with Homeopathically Prepared Thyroxin (10-11–10-21) - Gerhard Lingg; P. Christian Endler; Michael Frass; Harald Lothaller (The Scientific World Journal)
The influence of moderately diluted, agitated, i.e., homeopathically prepared, thyroxin solutions (10-11–10-12, final concentration in the basin water 0.6 × 10-15 − 0.6 × 10-25 parts by weight after the first application) on metamorphosis in highland Rana temporaria from the two-legged stage was studied. In accordance with the homeopathic idea of effects of specially prepared dilutions being inverse to those of their mother substances, animals were treated either with thyroxin 10-11–10-21 or analogously prepared blank solution (water). Development was monitored by documenting the number of animals that had entered the four-legged stage. It has been found that animals treated with the thyroxin solutions metamorphosed more slowly than the control animals, i.e., the effect of the homeopathically prepared thyroxin was opposed to the usual effect of molecular thyroxin. The number of test animals that reached the four-legged stage at defined points in time was smaller (2–13.5%) in the group treated with homeopathically prepared thyroxin at the points in time, compared to control. The results in this study sustain the previous multiresearcher findings that show that diluted homeopathically prepared thyroxin is able to slow down metamorphosis of R. temporaria.